Creating novel approaches to mitigate aflatoxin risk in food and feed with lactic acid bacteria: Fungal growth inhibition - Ahlberg, Sara H.; Korhonen, H.; Joutsjoki, V. (International Livestock Research Institute, 2014)
Aflatoxins, produced by Aspergillus fungi, are ubiquitous toxins and they can present a severe health risk to humans and animals if contaminated food and feed is consumed. Fungi live in the soil and on the surface of the crop and Aspergillus species are dominant in favorable conditions of maize cultivation areas. A novel biological method could reduce the health risks of aflatoxins through inhibiting mold growth and thus aflatoxin production. Lactic acid bacteria (LAB) are commonly used in fermented food production; they are also known to inhibit mold growth. Mold growth inhibition by certain LAB strains may be caused by competition for living conditions between bacterial cells and fungi and/or production of antifungal compounds such as organic acids. 200 LAB strains of bacteria have been isolated from 21 different indigenous fermented dairy and cereal products prepared locally in different parts of Kenya. These strains are being tested for their growth inhibition abilities against aflatoxin producing Aspergillus fungi in laboratory conditions. Later, these same effective strains will be tested in various food and feed matrices against Aspergillus growth and then the ones with most potential will be identified. Novel biological methods can have a role in preventing toxic effects of aflatoxins in food and feed. Exploitation of LAB is a good option for existing methods as LAB are generally recognized as safe.